Variación estacional del fitoplancton en la cuenca inferior del Río Salado (provincia de Buenos Aires) - Bazzuri, María Elisa (2008)
The main aim of this survey was to analyze seasonal variations in phytoplankton composition, relating its behaviour to temperature and conductivity, at El Destino (ED) sampling site in the Salado river lower-basin. A total of 28 phytoplankton samples were taken twice a week from 9/3 to 20/7/2004 and were analysed according to Utermöhl method. In total, 145 algae taxa were identified, although rare species were discarded in order to avoid statistical misinterpretation. Correlation coefficients and autocorrelation analyses (Q-Ljung-Box statistic) were performed in order to establish seasonal patterns of species abundance. Significant autocorrelations (p <0.05) were observed between phytoplankton species and temperature-conductivity patterns, thus illustrating their seasonal behaviour. Moreover, taxa were grouped according to their occurrence during different water temperature periods: (1) a ‘summer’ group, included 41 species that were well represented during warm-waters (>22ºC) like Planctonema lauterbornii, Chondrocystis dermochroa, Geminella interrupta, Chrooccocus spp., Merismopedia spp., among others; (2) a ‘winter’ group, which included 10 species whose highest densities were reached during the cold-waters period (<12ºC) for e.g. Binuclearia sp, Nitzschia fruticosa, Schroederia indica, Microcystis firma; (3) a ‘transitional’ group, of only 4 species with abundance peaks during ‘intermediate’ conditions (15.5ºC average) with Closteriopsis acicularis and Nodularia spumigena being the most remarkable; and (4) an ‘indifferent’ group, with 29 species of random behaviour whose autocorrelations remain within confidence limits, like Thorakochloris nygaardii, Pseudoanabaena limnetica, Monoraphidium giffithii, Scenedesmus linearis, etc. An evident seasonal succession was detected, having species substitution from summer warm-stagnant adapted species to cold-waters favoured ones, hence indicating different successional stages.